2009
DOI: 10.1161/circulationaha.109.863084
|View full text |Cite
|
Sign up to set email alerts
|

Early Tissue Distribution of Bone Marrow Mononuclear Cells After Intra-Arterial Delivery in a Patient With Chronic Stroke

Abstract: A 24-year-old man with a cerebral infarct within the left middle cerebral artery (MCA) territory was enrolled in a study to assess the safety of autologous bone marrow mononuclear cell (BMMC) transplantation in patients with ischemic stroke (NCT00473057). His National Institutes of Health Stroke Scale score was 7. Computed tomography ( Figure 1A) and technetium-99m ethyl cysteinate dimer ( 99m Tc ECD) single photon emission computed tomography (SPECT) (Figures 1B and 2 and Movie I in the online-only Data Supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 4 publications
2
21
0
2
Order By: Relevance
“…Although there are no accepted techniques to label and monitor cells for clinical testing, several approaches are currently available, including iron, indium, thallium, gadolinium-based agents, etc. 14,15 More investigation is urgently needed to develop safe and reliable labeling techniques for deployment in clinical trials. Whatever labeling approach is chosen, it is important to assess that the label does not impair viability of the cellular product.…”
Section: Role Of Imaging In Clinical Trialsmentioning
confidence: 99%
“…Although there are no accepted techniques to label and monitor cells for clinical testing, several approaches are currently available, including iron, indium, thallium, gadolinium-based agents, etc. 14,15 More investigation is urgently needed to develop safe and reliable labeling techniques for deployment in clinical trials. Whatever labeling approach is chosen, it is important to assess that the label does not impair viability of the cellular product.…”
Section: Role Of Imaging In Clinical Trialsmentioning
confidence: 99%
“…Local 18 F-FDG uptake increased at varying degrees approximately 6 mo after cell therapy (19). 99m Tc-labeled bone marrow mononuclear cells accumulated in the area of middle cerebral artery stroke demonstrated by 99m Tcethyl cysteinate dimer 2 h after cell transplantation (20). Similarly, 99m Tchexamethylpropylene amine oximelabeled autologous bone marrow mononuclear cells accumulated in the area of stroke within 8 h after cell delivery, whereas whole-body images showed tracer distribution in the liver and spleen (21).…”
Section: When These Cells Are Used For Medicalmentioning
confidence: 99%
“…Barbosa da Fonseca et al [86,87] and Battistella et al [88], respectively, reported the imaging and clinical results of a trial that included six patients 59 to 82 days after an MCA ischemic stroke. Afterward, another case where cells were injected 19 days after the stroke was also reported [89].…”
Section: Autologous Bm-mncsmentioning
confidence: 99%